Conducting assessment instrument models for teacher competence, teacher welfare as an effort to enhance education quality - Maba, Wayan; Perdata, Ida Bagus Ketut; Astawa, I Nengah; Mantra, Ida Bagus Nyoman (International Research Journal of Management, IT & Social Sciences, 2018)
Teacher competence and teacher welfare are essential aspects to successfully improve education quality. Assessment instrument models for teacher competence and teacher welfare therefore important to be developed to meet the required standards. This study aims at developing a set of assessment instrument models for teacher competence, teacher welfare, and educational quality improvement. The study was designed for two years adopting the Research and Development method employing 4D models consisting of Define, Design, Develop and Disseminate. The result of this study is in the form of assessment models for teacher competence, teacher welfare, and quality of education which have been validated by selected teachers, principals, and school supervisors. This assessment models have strong beneficial significance to the improvement of education quality and teacher professional development.